1996
DOI: 10.1159/000179178
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin, a Potent Microcirculatory Effector, Is Not Angiogenic

Abstract: The ability of relaxin (RLX), which is a potent microcirculatory effector in many species including the rat, to induce de novo angiogenesis in vascularized mammalian tissue was tested using the rat mesenteric-window angiogenesis assay. RLX was administered intraperitoneally on days 1-5 at doses of 0.33, 3.3 and 33 nM. Controls received the vehicle by the same route. Groups of animals were sacrificed at the end of the 1st, 2nd and 3rd weeks. Using computer-aided microscopic morphometry including image analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…In vivo, many pharmacological studies, as well as toxicology safety studies, using systemic administration of relaxin have shown the absence of any angiopathies or hypotension associated with systemic administration of cytokines known to have direct effects on endothelial cells, such as VEGF or bFGF. Previous reports have shown directly that relaxin infusion into a normal omental vascular bed will not cause proliferation of vessels 16 . This finding is consistent with the hypothesis that endothelial cells do not proliferate when exposed to relaxin.…”
Section: Resultssupporting
confidence: 90%
“…In vivo, many pharmacological studies, as well as toxicology safety studies, using systemic administration of relaxin have shown the absence of any angiopathies or hypotension associated with systemic administration of cytokines known to have direct effects on endothelial cells, such as VEGF or bFGF. Previous reports have shown directly that relaxin infusion into a normal omental vascular bed will not cause proliferation of vessels 16 . This finding is consistent with the hypothesis that endothelial cells do not proliferate when exposed to relaxin.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, VEGF mRNA expression was not enhanced by rhRLX in resident macrophages in the lung or spleen remote from the site of injury. Nor did rhRLX have any direct angiogenic effects on cultured endothelial cells, confirming an earlier report (73). Finally, rhRLX increased VEGF 165 and 120, as well as bFGF mRNA expression by THP-1 cells, a human monocyte/macrophage cell line.…”
Section: Rlx and Angiogenesissupporting
confidence: 87%
“…Computer-assisted morphometry of sinusoids was performed on the semithin sections as described previously for similar purposes (Norrby et al 1996). Two different liver fragments per rat were used.…”
Section: Liver Sinusoids and Relaxin · D Bani And Others 543mentioning
confidence: 99%